Facebook Sebagai Media Promosi (Studi Deskriptif Kualitatif Jejaring Sosial Facebook Sebagai Media Promosi pada Buck Photography) - Timor, Verdha Ritno (2016)
In recent years, new media has been finding new excitement with the emergence of Facebook social media. The site provides in virtual world a place to make a community of friendship that can be accessed by people of the world. Interactive capability of the online media is able to provide direct feedback so that interpersonal communication is created. Users who are enthusiastic in promoting goods and services uses popularity of the Facebook as a good media of sales. Buck Photography has been trying to take the opportunity. Various strategies have been performed to maintain its existence in a competing photographic industry. The Buck Photography is a small business providing camerawork so that budget of promotion activity should be estimated carefully. Therefore, the small business chooses Facebook as an alternative media to make online promotion activity. Purpose of the research is to know role of Facebook as communication media of marketing of the Buck Photography. It is expected that the research can be useful for people about importance of a marketing communication and also selection of appropriate media according to product and service to offer by marketer. The research is descriptive-qualitative one, namely it describe an object as a fact found in field. Data validity of the research was examined by using data reduction, data presentation, and conclusion drawing. The research concluded that Buck Photography had applied SWOT analysis as a marketing analysis, and then, it implemented strategies of marketing communication, namely advertising, sales promotion, and direct sales. Facebook social network was used as media of promotion.